Partially defatted chia flour as a novel ingredient for gluten-free breadmaking: Improving sustainability, nutrition and consumer liking - Fernanda Garcia dos Santos; Luciana Sandri; Urszula Krupa-Kozak; Vanessa Dias Capriles (Future Foods)
Partially defatted chia flour (DCF) is a valuable food ingredient in the context of a circular economy, with the potential to improve the nutrient and bioactive contents of gluten-free foodstuff. Thus, this study assessed the effects of interactions between DCF and water content (W) on the physical and sensory properties of gluten-free bread (GFB) and defined, using the response surface method, the composition of formulations that enable quality optimization. A rotatable central composite design was used to assess the main and interaction effects of DCF (ranging from 0 to 28% on a flour basis (fb) and W (ranging from 100 to 200% fb) on the physical properties and consumer linking of rice flour based GFB. The resulting models indicated that higher DCF or W levels diminished the bread quality. However, different W and up to 17.2% DCF can be used to prepare bread with high consumer liking (scores ≥7 for all assessed characteristics, on a scale of 10). The formulation prepared with 0% DCF and 135.5% W (fb) had the highest degree of liking (varying from 8.3 to 9.0). However, when incorporating up to 9.8% DCF and 135.5% W, a high liking can be maintained (scores 8.0 to 8.5 for all characteristics). Acceptable GFB with up to 17.2% DCF in the formulation can be obtained if the W content is adjusted (135 to 139.7% fb). Incorporating 17.2% DCF doubles the fiber content of the GFB. Therefore, DCF is an alternative ingredient to obtain nutritionally improved and acceptable GFB.